Inverse of a function in a integral

Calculus Level 3

0 1 ( ( 1 x 18 ) 1 20 ( 1 x 20 ) 1 18 ) d x \large \int_{0}^{1}\left((1-x^{18})^\frac{1}{20}-(1-x^{20})^\frac{1}{18}\right) dx

Evaluate the integral above.


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

ChengYiin Ong
Aug 2, 2019

Let's find a relationship between ( 1 x 18 ) 1 20 (1-x^{18})^\frac{1}{20} and ( 1 x 20 ) 1 18 (1-x^{20})^\frac{1}{18} , as you may guess from the title, they are inverses of each other.

This is because if we let the following:

y = ( 1 x 18 ) 1 20 y 20 = 1 x 18 x = ( 1 y 20 ) 1 18 . y=(1-x^{18})^\frac{1}{20} \Rightarrow y^{20}=1-x^{18} \Rightarrow x=(1-y^{20})^\frac{1}{18}. which shows that they are inverses of each other.

Since we are integrating the function from 0 0 to 1 1 , we can check that the function and the inverse have the same area.

This is true if we plug in the values of x = 0 , 1 x=0,1 into y = ( 1 x 18 ) 1 20 y=(1-x^{18})^\frac{1}{20} we will get y = 1 , 0 y=1,0

Then,

0 1 ( 1 x 18 ) 1 20 ( 1 x 20 ) 1 18 d x \int_{0}^{1}(1-x^{18})^\frac{1}{20}-(1-x^{20})^\frac{1}{18}dx

= 0 1 ( 1 x 18 ) 1 20 d x 0 1 ( 1 x 20 ) 1 18 d x =\int_{0}^{1}(1-x^{18})^\frac{1}{20}dx-\int_{0}^{1}(1-x^{20})^\frac{1}{18}dx

= 0 1 ( 1 x 18 ) 1 20 d x 0 1 ( 1 y 18 ) 1 20 d y =\int_{0}^{1}(1-x^{18})^\frac{1}{20}dx-\int_{0}^{1}(1-y^{18})^\frac{1}{20}dy

= 0. =0.

I = 0 1 ( ( 1 x 18 ) 1 20 ( 1 x 20 ) 1 18 ) d x = 0 1 ( 1 x 18 ) 1 20 d x 0 1 ( 1 x 20 ) 1 18 d x Let u = x 18 d u = 18 x 17 d x = 0 1 ( 1 u ) 1 20 18 u 17 18 d u 0 1 ( 1 v ) 1 18 20 v 19 20 d v Let v = x 20 d v = 20 x 19 d x = 1 18 B ( 1 18 , 21 20 ) 1 20 B ( 1 20 , 19 18 ) Beta function B ( m , n ) = 0 1 t m 1 ( 1 t ) n 1 d t = Γ ( 1 18 ) Γ ( 21 20 ) 18 Γ ( 199 180 ) Γ ( 1 20 ) Γ ( 19 18 ) 20 Γ ( 199 180 ) B ( m , n ) = Γ ( m ) Γ ( n ) Γ ( m + n ) , where Γ ( ) denotes gamma function = Γ ( 1 18 ) 1 20 Γ ( 1 20 ) 18 Γ ( 199 180 ) Γ ( 1 20 ) 1 18 Γ ( 1 18 ) 20 Γ ( 199 180 ) Note that Γ ( 1 + x ) = x Γ ( x ) = 0 \begin{aligned} I & = \int_0^1 \left((1-x^{18})^\frac 1{20} - (1-x^{20})^\frac 1{18}\right) dx \\ & = {\color{#3D99F6}\int_0^1 (1-x^{18})^\frac 1{20} dx} - \color{#D61F06} \int_0^1 (1-x^{20})^\frac 1{18} dx & \small \color{#3D99F6} \text{Let }u = x^{18} \implies du = 18 x^{17} dx \\ & = {\color{#3D99F6}\int_0^1 \frac {(1-u)^\frac 1{20}}{18u^\frac {17}{18}} du} - \color{#D61F06} \int_0^1 \frac {(1-v)^\frac 1{18}}{20v^\frac {19}{20}} dv & \small \color{#D61F06} \text{Let }v = x^{20} \implies dv = 20 x^{19} dx \\ & = \frac 1{18}\text{B}\left(\frac 1{18}, \frac {21}{20}\right) - \frac 1{20}\text{B}\left(\frac 1{20}, \frac {19}{18}\right) & \small \color{#3D99F6} \text{Beta function }\text B (m,n) = \int_0^1 t^{m-1}(1-t)^{n-1} dt \\ & = \frac {\Gamma \left(\frac 1{18}\right) \Gamma \left(\frac {21}{20}\right)}{18 \Gamma \left(\frac {199}{180}\right)} - \frac {\Gamma \left(\frac 1{20}\right) \Gamma \left(\frac {19}{18}\right)}{20 \Gamma \left(\frac {199}{180}\right)} & \small \color{#3D99F6} \text B (m,n) = \frac {\Gamma (m) \Gamma (n)}{\Gamma (m+n)} \text{, where }\Gamma(\cdot) \text{ denotes gamma function} \\ & = \frac {\Gamma \left(\frac 1{18}\right) \cdot \color{#3D99F6}\frac 1{20}\Gamma \left(\frac 1{20}\right)}{18 \Gamma \left(\frac {199}{180}\right)} - \frac {\Gamma \left(\frac 1{20}\right) \cdot \color{#3D99F6} \frac 1{18} \Gamma \left(\frac 1{18}\right)}{20 \Gamma \left(\frac {199}{180}\right)} & \small \color{#3D99F6} \text{Note that }\Gamma (1+x) = x\Gamma (x) \\ & = \boxed 0 \end{aligned}


References:

Priyanshu Mishra
Aug 5, 2019

Coz you know the identity;

a b f ( x ) d x + f ( a ) f ( b ) f 1 ( x ) d x = b f ( b ) a f ( a ) \large\ \displaystyle \int_{a}^{b} f(x)dx + \int_{f(a)}^{f(b)} f^{-1}(x)dx = bf(b) - af(a)

the rest is a big ZERO.

There is a slight typo on the second integral. Where it says f ( f 1 ( x ) ) f(f^{-1}(x)) , it should be just f 1 ( x ) f^{-1}(x) .

Pedro Cardoso - 1 year, 10 months ago

Log in to reply

Oh yeah, thanks mate.

Priyanshu Mishra - 1 year, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...